Implementasi Peraturan Bupati Gianyar Nomor 57 Tahun 2018 terhadap Penyediaan Fasilitas Parkir di Kawasan Pariwisata Ubud - Anak Agung Istri Pradnya Paramitha; Anak Agung Sagung Laksmi Dewi; I Nyoman Sutama (Warmadewa Press, 2020)
Changing the habits of tourists and the community using the road as a parking lot is still considered truly difficult. Efforts made by the government, such as providing a parking center and firm action for offenders who still use the road as a parking lot in the Ubud tourism area, have also not been able to solve this problem. The problems discussed in this study are the effectiveness of the implementation of the Gianyar Regent Regulation (Perbup) Number 57 of 2018 related to the provision of parking facilities in the Ubud tourism area and the factors that influence the occurrence of parking violations in the tourism area. The research was designed using empirical legal research which is also known as field research. The results of the study reveal that the effectiveness of the implemention of the Gianyar Perbup Number 57 of 2018 related to the provision of parking facilities in the Ubud tourism area has not been effective because of the many parking problems existing in the area. The factors influencing the occurrence of parking rules violations in the parking area include internal factor and external factor. Firmness from the implementing agency of the Perbup is needed so that the regulation can be more effective and the vehicle owners are expected not to park their vehicles carelessly.